The Assyrian King List from Khorsabad - Poebel, A.
concluded; Poebel’s latest article puts 6 usurpers, epding with Adasi, father of Bêlu-bâni (in ‘1648 B. C.’), Aššurrabi I son of (Enlil-naṣir I) follows Aššuršadûni (Aššuršadṣabe, Weidner) son of Nûrili immediately, and Weidner’s three intervening kings are duplications. Poebel gets down to Enlil-kudur-uṣur, son of Tukulti-Ninurta I, giving ‘1196-2 B. C.’. No facsimile or transcription.